Contemporary France - Hanley, D. L.; Kerr, A. P.; Kerr, Miss A P; Waites, N. H. (Taylor & Francis, 1985)
First published in 1984. Routledge is an imprint of Taylor & Francis, an informa company.
English
Keywords: Humanities; gaulle; fourth; republic; monde; couve; murville; chef; cabinet; force; frappe